Solar flare induced D-region ionospheric perturbations evaluated from VLF measurements - Singh, Ashutosh K.; Singh, A. K.; Singh, Rajesh; Singh, R. P. (My University, 2014)
The results of very low frequency (VLF) wave amplitude measurements carried out at the low latitude station Varanasi (geom. lat. 14∘55′N, long. 154∘E), India during solar flares are presented for the first time. The VLF waves (19.8 kHz) transmitted from the NWC-transmitter, Australia propagated in the Earth-ionosphere waveguide to long distances and were recorded at Varanasi. Data are analyzed and the reflection height H′ and the sharpness factor β are evaluated. It is found that the reflection height decreases whereas sharpness factor increases with the increase of solar flare power. The H′ is found to be higher and β smaller at low latitudes than the corresponding values at mid and high latitudes. The sunspot numbers were low during the considered period 2011–2012, being the rising phase of solar cycle 24 and as a result cosmic rays may impact the D-region ionosphere. The increased ionization from the flare lowers the effective reflecting height, H′, of the D-region roughly in proportion to the logarithm of the X-ray flare intensity from a typical mid-day unperturbed value of about 71–72 km down to about 65 km for an X class flare. The sharpness (β) of the lower edge of the D-region is also significantly increased by the flare but reaches a clear saturation value of about 0.48 km−1 for flares of magnitude greater than about X1 class.
Keywords: Sun-flares; X-rays; VLF waves; Ionospheric perturbations; Very low frequency; Solar flare